Wollastonite as adsorbent for removal of Fe(II) from water - Singh A.K.; Singh D.P.; Panday K.K.; Singh V.N. (My University, 2025)
Wollastonite was used as an adsorbent for the removal of Fe(II) at different experimental conditions. The extent of removal is favourable at low concentration and low temperature. Maximum adsorption was noted at pH 4.0. The batch adsorption kinetics has been described by a first order rate expression, and the surface mass transfer coefficients and diffusion coefficients have been calculated at different temperatures. The intraparticle transport of Fe(II) within the pores of wollastonite is found to be the rate limiting step. The applicability of the Langmuir isotherm for the present system has been tested at different temperatures. Thermodynamic parameters indicate the exothermic nature of Fe(II) adsorption on wollastonite. The variation of adsorption with pH has been explained on the basis of interaction of iron species with negatively charged constituents of adsorbent. Copyright © 1988 Society of Chemical Industry